MOTIVASI SISWA DALAM PEMBELAJARAN SENI TARI DI KELAS VII-1 SMP NEGERI 12 PADANG - Ngaini, Rifha; Susmiarti, Susmiarti (SENDRATASIK UNP, 2019)
AbstractÂ The purpose of this research is to describe the students ' motivation for the art of dance in class VII-1 in Padang Negeri 12. This type of research is qualitative research with descriptive methods of analysis. The instruments in this research are researchers themselves and are assisted by stationery and cameras. The data types in this study are primary data and secondary data. Data collection techniques are conducted by way of library studies, observation and documentation. The steps for analyzing data are data collection, describing data, identifying data and making conclusions. The results showed that students ' motivation in dance learning in SMP Negeri 12 Padang is influenced by intrinsic factors (from inside) and extrinsic (from outside) students, thus causing the differences in the students ' ability to learn dance. Individually and in groups. If viewed individually, the motivation to learn the dance of each grade VII-1 students is low, proven from the low learning outcomes of individual students in the field of knowledge (theory) and Skills (practice) dance. However, when viewed in groups, the motivation to learn dance from the group of Students dance Learning class VII-1 for training activities, especially higher. These differences show that learning dance especially in the field of practice is conducted in groups by students, extrinsic has improved the learning outcomes of students in the group. Because of cooperation, mutual help, and a healthy sense of competitiveness between groups, has been driving the students are less able to learn to improve the results of dance learning together in the group.Â Keywords: motivation; Learning Dance Art